Ligand selectivity in tachykinin and natalisin neuropeptidergic systems of the honey bee parasitic mite Varroa destructor - Jiang, H.; Kim, D.; Dobesh, S.; Evans, J. D.; Nachman, R. J.; Kaczmarek, K.; Zabrocki, J.; Park, Yoonseong (My University, 2016)
The varroa mite, Varroa destructor, is a devastating ectoparasite of the honey bees Apis mellifera and A. cerana. Control of these mites in beehives is a challenge in part due to the lack of toxic agents that are specific to mites and not to the host honey bee. In searching for a specific toxic target of varroa mites, we investigated two closely related neuropeptidergic systems, tachykinin-related peptide (TRP) and natalisin (NTL), and their respective receptors. Honey bees lack both NTL and the NTL receptor in their genome sequences, providing the rationale for investigating these receptors to understand their specificities to various ligands. We characterized the receptors for NTL and TRP of V. destructor (VdNTL-R and VdTRP-R, respectively) and for TRP of A. mellifera (AmTRP-R) in a heterologous reporter assay system to determine the activities of various ligands including TRP/NTL peptides and peptidomimetics. Although we found that AmTRP-R is highly promiscuous, activated by various ligands including two VdNTL peptides when a total of 36 ligands were tested, we serendipitously found that peptides carrying the C-terminal motif-FWxxRamide are highly specific to VdTRP-R. This motif can serve as a seed sequence for designing a VdTRP-R-specific agonist.
Citation: Jiang, H., Kim, D., Dobesh, S., Evans, J. D., Nachman, R. J., Kaczmarek, K., . . . Park, Y. (2016). Ligand selectivity in tachykinin and natalisin neuropeptidergic systems of the honey bee parasitic mite Varroa destructor. Scientific Reports, 6, 8. doi:10.1038/srep19547
Keywords: Tick Ixodes-Scapularis; Functional-Characterization; Insect; Neuropeptides; Locustatachykinin-I; Diapause Hormone